2011
DOI: 10.1542/peds.2010-1821
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function After Intrauterine Growth Restriction and Very Preterm Birth

Abstract: Children born very preterm after IUGR have an increased risk for cognitive impairment at early school age compared with children delivered very preterm for other reasons. Differences in cognitive outcome were restricted to boys who may have been especially vulnerable to the influence of IUGR and very preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
129
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(147 citation statements)
references
References 41 publications
12
129
2
4
Order By: Relevance
“…This was associated with long‐term intrauterine complications, including IUGR and maternal hypertension. IUGR results from placental insufficiency, increases risk for adverse outcome in preterm infants, and, on occasion, may share a common pathogenesis with maternal hypertension 14, 41. It has previously been difficult to dissociate adverse antenatal and postnatal correlates of abnormal brain development.…”
Section: Discussionmentioning
confidence: 99%
“…This was associated with long‐term intrauterine complications, including IUGR and maternal hypertension. IUGR results from placental insufficiency, increases risk for adverse outcome in preterm infants, and, on occasion, may share a common pathogenesis with maternal hypertension 14, 41. It has previously been difficult to dissociate adverse antenatal and postnatal correlates of abnormal brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Morsing et al. 28 described a relationship between intrauterine growth restriction due to absent or reversed end‐diastolic blood flow in the umbilical artery and poor cognitive function among boys of school age. The incidence of intrauterine growth retardation was not known in this study, as we lacked data on intrauterine ultrasound examinations of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to some other studies that had reported lower total IQ in SGA children (6,9), our findings suggest that being born preterm affects IQ more than does growth restriction. This is more so in verbal IQ than in performance IQ (10). A large population based cohort study reported follow up data of the EPIPAGE cohort at 5 y of age (6).…”
Section: Discussionmentioning
confidence: 99%
“…Some stud ies report lower IQ scores (6,9,10) and more behavioral problems or attention deficits in these children (9) as compared with con trols (6), whereas others have found no differences as regards behavioral problems and attention deficits (6,10). Cognitive impairment was restricted to verbal IQ only (10). Several specific neuropsychologic functions such as motor skills, executive func tioning, memory, visuomotor integration, and visual perception were not studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation